The COVID-19 pandemic and its impact on health experiences of asylum seekers to the United States - Elizabeth Singer; Kevin Molyneux; Mahalya Gogerly-Moragoda; Dustin Kee; Kim A. Baranowski (BMC, 2023)
Abstract Background The COVID-19 pandemic exacerbated preexisting barriers to accessing healthcare and social services faced by asylum seekers to the United States. This study aimed to uncover the impact of the first year of the COVID-19 pandemic on asylum seekers, including socio-economic stressors and access to medical information, healthcare, and testing. Method We conducted 15 semi-structured, in-depth interviews with adult asylum seekers to the U.S. and systematically analyzed the resulting transcripts using a consensual qualitative research approach. Results The transcripts yielded six domains: (1) knowledge and understanding of COVID-19; (2) attitudes and practices relating to COVID-19 precautions; (3) experience of COVID-19 symptoms; (4) current physical and mental health; (5) access to and interaction with health care; (6) discrimination based on asylum status. Conclusions Although participants had knowledge about COVID-19's communicability and regularly used masks, their living conditions frequently hindered their ability to quarantine and isolate, and their lack of insurance was often a deterrent to them seeking medical care. Notably, immigration status was not a significant factor discouraging participants from seeking care during the pandemic. The findings build on existing knowledge about this community and may help define areas where support and services can be expanded in current and future pandemics.